2018
DOI: 10.1002/ijgo.12423
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular biochemical risk factors among women with spontaneous preterm delivery

Abstract: An association between sPTD and unfavorable lipids and cardiovascular biochemical risk factors was not established. The higher levels of glucose in the sPTD group might be due to increased insulin resistance, which is associated with a higher risk of sPTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Pregnancies with poorly controlled GDM have also been shown to have higher rates of preterm delivery compared to normal pregnancies [23]. Lastly, higher average glucose values are seen in normal pregnancies who experience spontaneous preterm delivery compared to controls with spontaneous term labor [24]. Applied to our findings, the above hypothesis would argue that the lower glycemic target group allowed more GDM pregnancies to reach 39 weeks, at which point they were recommended for induction of labor.…”
Section: Discussionmentioning
confidence: 53%
“…Pregnancies with poorly controlled GDM have also been shown to have higher rates of preterm delivery compared to normal pregnancies [23]. Lastly, higher average glucose values are seen in normal pregnancies who experience spontaneous preterm delivery compared to controls with spontaneous term labor [24]. Applied to our findings, the above hypothesis would argue that the lower glycemic target group allowed more GDM pregnancies to reach 39 weeks, at which point they were recommended for induction of labor.…”
Section: Discussionmentioning
confidence: 53%
“…However, the evidence from this study would indicate that our current scientific understanding of the relationship between lipid metabolism, PTB, and genetics is incomplete. Although some studies have found increased risk for PTB among women with low TC during pregnancy or at delivery, (Edison et al, ; Heida et al, ; Oluwole et al, ) associations between high HDL‐C or low TAG and increased risk for PTB have not been previously identified. In interpreting these findings, it is important to recognize the degree to which the GRS explain variability in the lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…Kaser et al (2001) evaluated lipid levels in infants and reported small for gestational age (SGA) neonates to have lower HDL, LDL, and TC levels, compared to appropriate for gestational age (AGA) infants [27]. Moreover, Heida et al (2017) found no correlations between spontaneous preterm delivery and unfavourable lipid levels or cardiovascular biochemical risk factors in mothers [14]. Grace et al (2017) examined the relationship between maternal serum lipoproteins and gestational age, and reported LDL and HDL concentrations to be independently related with gestational age at preterm delivery [28].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that the risk of spontaneous preterm delivery could be increased by high TG levels, but was not affected by HDL-C and LDL-C levels [13]. Meanwhile, Heida et al (2017) reported lower TC and LDL-C levels in women with spontaneous preterm delivery, but could not establish a significant relationship between undesirable lipid levels and preterm delivery [14]. Since changes in fat metabolism during pregnancy can be associated with adverse pregnancy outcomes, this review aimed to determine the association between lipid profiles during pregnancy and preterm delivery.…”
Section: Introductionmentioning
confidence: 99%